(untitled) (Strathmore Law Journal, 2017)
The United Nations Security Council (UNSC) increasingly emphasises the need for a comprehensive approach to countering the spread of terrorism and violent extremism. In its Resolution 2178 (2014), the UNSC encourages member statesm to engage with relevant local communities and non-governmental actors in developing strategies to counter the violent extremist narrative that can incite terrorist acts. The role played by the African Commission on Human and Peoples’ Rights in the struggle against terrorism is really important. The African approach to human rights has decisively contributed to understanding, preventing and countering this phenomenon. In this line, Article 23(1) of the African Charter on Human and Peoples’ Rights (African Charter) states that all peoples shall have the right to national and international peace and security, as well as the principles of friendly relations among states, which form the basic foundation of the African Union. The African Charter does not contain enough directives to aid the enforcement of the right. The African Charter limits the whole question of peace to ensuring that an asylum-seeker does not engage in subversive activities against the country of origin or any other State Party to the African Charter, and provides a prohibition to the use of the territory of a member state for subversive or terrorist activities. Finally, on 18 November 2016, the Third Committee of the General Assembly of the United Nations adopted the Declaration on the Right to Peace, whose preambular section not only deeply deplored all acts of terrorism, but also stressed that all measures taken in the fight against terrorism must be in compliance with the obligations of states under international law.